2018
DOI: 10.1097/ncc.0000000000000661
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hematologic Cancer and Its Treatment on Physical Activity Level and Quality of Life Among Children in Mainland China

Abstract: Background: The effects of hematologic cancer and its treatment on Chinese children's physical activity level and quality of life (QoL) remain unclear despite numerous studies conducted in Western countries and Hong Kong. Objective: To examine the effects of hematologic cancer and its treatment on the physical activity level and QoL among Chinese children. Methods: A cross-sectional study was conducted. One hundred twenty-five children who were admitted for treatment of hematologic cancer and 243 healthy count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…In Mainland China, most health behaviour research concentrated on healthy children or adult groups. Only a few studies documented PA and QoL among paediatric patients with cancer during the treatment period, which identified that PA level and QoL among this population were both lower than healthy peers, and lacking PA had significant negative effects on their QoL (Ouyang et al, 2019; Xia et al, 2018). However, research on these children entering survivorship is still blank; the health behaviours and QoL of Chinese CCS remain unclear despite numerous research conducted in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…In Mainland China, most health behaviour research concentrated on healthy children or adult groups. Only a few studies documented PA and QoL among paediatric patients with cancer during the treatment period, which identified that PA level and QoL among this population were both lower than healthy peers, and lacking PA had significant negative effects on their QoL (Ouyang et al, 2019; Xia et al, 2018). However, research on these children entering survivorship is still blank; the health behaviours and QoL of Chinese CCS remain unclear despite numerous research conducted in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…These prevalence rates were all higher than those of Western CCSs (45% of insufficient PA and 32% of exceeded screen time in 5- to 15-year-olds 41 ) or local healthy children and adolescents (65.9% of insufficient PA and 34.6% of exceeded screen time in 7- to 19-year-olds, 42 14.1% of internet addiction in 11- to 20-year-olds 43 ). Frequent treatment and adverse effects may also undermine children’s PA, which can contribute to fatigue, depressive symptoms, and severely limited mobility, forcing them to rest more and further increase screen time, risking internet addiction 44 . As children enter survivorship, these poor behaviors may linger.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer and anticancer therapies are associated with many adverse effects on childhood cancer survivors (CCSs). Research has shown that, during treatment, CCSs may experience fatigue and a decline in cardiopulmonary function, muscle strength, functional performance, and quality of life (QoL) [ 1 , 2 , 3 ]. Although, the five-year survival rate of children diagnosed with cancer has reached nearly 85% due to the significant advancements in cancer treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%